1.7) Given "\\phi(x) = a e^x + b e^{cx}" is solution of "y''+y' - 2y = 0, y(0)=2,y'(0)=1".
Hence, "y = ae^x+be^{cx} \\implies y' = ae^x+bce^{cx} \\ and \\ y'' = ae^x+bc^2e^{cx}".
So, "(ae^x+bc^2e^{cx}) + (ae^x+bce^{cx}) - 2(ae^x+be^{cx}) = 0"
"\\implies b(c^2+c-2) = 0" _____________(1)
Also, "y(0)=2, y'(0)=1"
"\\implies a+b=2" __________________(2)
and "a+bc = 1" ___________________(3)
From equation(1) if "b = 0" , then from equation(2) "a = 2" and from equation (3) "a = 1" which is not possible, so "b\\neq 0".
Now, so from equation(1), "c^2+c-2 = 0 \\implies (c+2)(c-1) = 0"
"\\implies either \\ c = 1, \\ or \\ c = -2."
If "c = 1," then from equation (3) "a+b = 1" which contradict the equation (2), so "c \\neq 1".
Only "c = -2" is possible, so from equation (3) "a-2b = 1" _____________(4).
So, by equation (2) - equation(3), we get "c = \\frac{1}{3}" and hence "a = \\frac{5}{3}" .
So, "a+b+c=2+(-2) = 0".
1.8) Given "x = at, y= -t^2" is solution of "y= x(dy\/dx) + (dy\/dx)^2".
Now, "\\frac{dx}{dt} = a, \\frac{dy}{dt} = -2t \\implies \\frac{dy}{dx} = \\frac{dy\/dt}{dx\/dt} = -\\frac{2t}{a}".
By putting in given differential equation, we get
"-t^2 = at (\\frac{-2t}{a}) + (\\frac{-2t}{a})^2 \\\\\n\\implies -a^2 t ^2= -2 a^2 t^2 + 4 t^2 \\implies a^2 = 4 \\\\ \\implies a = 2"
Comments
Leave a comment